Kaj prinaša prihodnji pokojninski sistem z vidika zagotavljanja medgeneracijske enakosti? - Rangus, Andraž (Delavci in delodajalci, 2016)
The current Law on Pension and Disability Insurance ensures medium-term sustainability of the system, but in the long-run does not meet the objective of financial balance of the pension exchequer. Unsustainable pension system requires an active approach of the legislator to decide about the future changes of the pension system, which will on the one hand ensure its sustainability and on the other, an adequate income for all future generations of pensioners. The White Paper on Pensions is the first step to forecast the changes in the pension system. It offers a range and combination of different measures to achieve these two objectives, the question remains, however, whether the proposed adjustments of the pension system ensure intergenerational equity.
Keywords: medgeneracijski odnosi; pokojninski sistemi; pokojninsko zavarovanje; socialna država